Sports plays - Laine, Eero, 1981-; Chow, Broderick (Routledge, 2022)
"Sport Plays is a volume about sports in the theatre and what it means to stage sports. The chapters in this volume examine sports plays through a range of critical and theoretical approaches that highlight central concerns and questions both for sports and for theatre. The plays cut across boundaries and genres, from Broadway-style musicals to dramas to experimental and developmental work. The chapters examine and trouble the conventions of staging sports as they open possibilities for considering larger social and cultural issues and debates. This volume's broad range of perspectives make it a compelling resource for students and scholars of sport, theatre, and performance studies whose interests span feminism, sexuality, politics, and race"--